The intercostobrachial nerve as a sensory donor for hand reinnervation in brachial plexus reconstruction is a feasible technique and may be useful for restoring sensation - Foroni, Luciano; Siqueira, Mário Gilberto; Martins, Roberto Sérgio; Oliveira, Gabriela Pintar (Arquivos de Neuro-Psiquiatria, 2017)
Few donors are available for restoration of sensibility in patients with complete brachial plexus injuries. The objective of our study was to evaluate the anatomical feasibility of using the intercostobrachial nerve (ICBN) as an axon donor to the lateral cord contribution to the median nerve (LCMN).Thirty cadavers were dissected. Data of the ICBN and the LCMN were collected, including diameters, branches and distances.The diameters of the ICBN and the LCMN at their point of coaptation were 2.7mm and 3.7mm, respectively. The ICBN originated as a single trunk in 93.3% of the specimens and bifurcated in 73.3%. The distance between the ICBN origin and its point of coaptation to the LCMN was 54mm. All ICBNs had enough extension to reach the LCMN.Transfer of the ICBN to the LCMN is anatomically feasible and may be useful for restoring sensation in patients with complete brachial plexus injuries.
Keywords: brachial plexus; intercostal nerves; median nerve; nerve transfer; sensation